Fitness Cost Associated With Enhanced EPSPS Gene Copy Number and Glyphosate Resistance in an Amaranthus tuberculatus Population - Cockerton, Helen M.; Kaundun, Shiv S.; Nguyen, Lieselot; Hutchings, Sarah Jane; Dale, Richard P.; Howell, Anushka; Neve, Paul (Frontiers in Plant Science, 2021)
The evolution of resistance to pesticides in agricultural systems provides an opportunity to study the fitness costs and benefits of novel adaptive traits. Here, we studied a population of Amaranthus tuberculatus (common waterhemp), which has evolved resistance to glyphosate. The growth and fitness of seed families with contrasting levels of glyphosate resistance was assessed in the absence of glyphosate to determine their ability to compete for resources under intra- and interspecific competition. We identified a positive correlation between the level of glyphosate resistance and gene copy number for the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) glyphosate target, thus identifying gene amplification as the mechanism of resistance within the population. Resistant A. tuberculatus plants were found to have a lower competitive response when compared to the susceptible phenotypes with 2.76 glyphosate resistant plants being required to have an equal competitive effect as a single susceptible plant. A growth trade-off was associated with the gene amplification mechanism under intra-phenotypic competition where 20 extra gene copies were associated with a 26.5 % reduction in dry biomass. Interestingly, this growth trade-off was mitigated when assessed under interspecific competition from maize.